The Interactive Local Wisdom E-Book with EARLS Features to Promote Tolerance Among Young Learners - Fina Zulfa Mustafidah; I Wayan Dasna; Dedi Kuswandi; Shirly Rizki Kusumaningrum (International Journal of Education and Teaching Zone, 2026)
This study aimed to develop and evaluate an interactive local wisdom based e-book integrated with the Environment Augmented Reality Learning System (EARLS) to support tolerance-oriented learning among elementary school students. EARLS is conceptualized as a pedagogical framework combining contextual cultural narratives, augmented reality based visualizations, reflective tasks, and collaborative learning activities to foster respect for diversity and cooperative behavior. A research and development approach based on the Lee and Owens model was employed, involving 17 fifth-grade students in a public elementary school in Indonesia during the field implementation phase. Tolerance was assessed through structured classroom observations, students’ performance on learning tasks, and pretest–posttest outcomes related to tolerance concepts. The findings indicate that the e-book demonstrates high feasibility and practicality, with moderate effectiveness reflected in improved student engagement and tolerance-related understanding. Beyond product validation, this study contributes theoretically by operationalizing EARLS as a culturally grounded augmented reality framework for character education, providing empirical insight into how local wisdom–based digital media can support tolerance development in primary education. However, results should be interpreted cautiously due to the small sample size and the one-group pretest–posttest design, which may limit generalizability. Future research involving larger samples and comparative designs is recommended to examine the broader applicability of EARLS-based local wisdom digital learning.